Demonstrating the principal mechanism of action of medical devices intended for vaginal use on reconstructed human vaginal epithelium: the case of two hyaluronic acid-containing devices - Meloni, Marisa; De Servi, Barbara; Carriero, Francesco; Simon O’Brien, Emmanuelle; Houamel, Dounia; Deruelle, Philippe; Castagné, Vincent (Frontiers in Drug Safety and Regulation, 2024)
Regulation (EU) 2017/745 on medical devices (MDR) has significantly modified the rules to be adopted for MD qualifications and classification. New requirements require robust evidence on mechanisms of action (MoAs) that cannot be produced by existing common EU or ISO standards. Therefore, on a “case-by-case basis,” a new evidence-based non-clinical approach to MD qualification must be defined. In this study, an in vitro experimental approach is described to assess the physicochemical and mechanical MoA of two hyaluronic acid (HA)-based medical devices: Mucogyne® Gel and Mucogyne® Ovule for vaginal use. They both act as moisturizers and lubricants as well as a healing adjuvant by promoting the continued moisture of the vulvovaginal area. The MoA of these two products has been demonstrated by using a 3D reconstructed human vaginal epithelium (HVE) model in a homeostatic physiological state and in stressed conditions. Film forming and persistency properties were assessed on intact HVE tissues by caffeine permeation assay and Lucifer Yellow (LY) localization on HVE vertical sections. Healing properties were assessed on injured HVE tissues by trans-electrical epithelial resistance (TEER) measurements associated with histo-morphological analysis (H&E), and moisturizing efficacy was evaluated on HVE tissues cultured in dry conditions by histomorphological analysis (H&E) and aquaporin 3 (AQP3) expression and localization by immunohistochemistry (IHC). Using the same “dry” HVE model, the non-pharmacological action of the two products was addressed by CD44 (hyaluronic acid receptor) expression and localization. The results suggest that in vitro evaluations can provide robust results on a human-relevant experimental model for the intended use of the products and supports clinical data with mechanistic information which may not be achieved with in vivo studies but are particularly important for product qualification. The results also underline the specific relative efficacy of the mechanisms investigated for Mucogyne® Gel and Mucogyne® Ovule in line with their different formulation types (respectively, hydrophilic and lipophilic) that influence the action of the active ingredient HA. The present in vitro non-clinical evaluation of HVE combined with clinical investigation data obtained in women explain why Mucogyne MDs provide significant benefits in various physiological or pathological situations, including vaginal dryness and healing.